Establishment of an indirect ELISA antibody detection method based on the stable expression of LSDV P32 protein in CHO-K1 cells - Ruolan Xin; Jiawen Zhang; Yinghui Zhang; Daoming Su; Menglin Li; Dan Liu; Ruizhi Wu; Junjie Zhao; Yuanyuan Zhu; Yebing Liu; Xiaoyun Chen; Yongjun Wen; et al. (BMC Biotechnology)
Abstract Background Lumpy skin disease (LSD), caused by infection with the lumpy skin disease virus (LSDV), is a highly infectious disease that poses a notable challenge to the cattle industry worldwide. To conduct epidemiological monitoring of LSDV infection in cattle and evaluate the immune efficacy of LSDV vaccines, it is essential to develop a rapid, sensitive, and specific ELISA-based antibody detection method. Results We utilized the LSDV P32 protein, stably expressed in a CHO-K1 suspension cell system, as a coating antigen to develop an indirect ELISA for Capripoxvirus (CaPV) antibody detection. This method specifically recognizes CaPV-positive sera without cross-reactivity with sera positive for bovine viral diarrhea virus, bovine rotavirus, infectious bovine rhinotracheitis virus, and Brucella antibodies. The method demonstrated a maximum serum dilution detection capacity of 1:3200, with intra- and inter-assay variation coefficients below 10%. Comparison with a commercially available kit showed an agreement of 95.7%. Conclusion The indirect ELISA antibody detection method established exhibited excellent specificity, sensitivity, and reproducibility, providing a reliable tool for clinical detection and epidemiological surveys of LSDV. This method offers significant potential for the prevention and control of LSD outbreaks.